An In-depth Review of Psychological Interventions to Address Depression for Children with Special Needs - Priambodo, Patera Adwiko (Actual Insight, 2024)
This think about points to investigate different comprehensive learning strategies for children with extraordinary needs, such as autism and Down syndrome, and identify challenges and solutions in addressing students' mental health issues in Indonesia. Using a Systematic Literature Review (SLR) approach, this study reviewed 195 publications and screened relevant articles for analysis. The discoveries illustrated the Islamic propensity demonstrate, Talaqqi wa Musyafahah, Al-Quran treatment, and game-based approach are great Islamic learning techniques for kids with extreme introvertedness and Down disorder. The biggest obstacles to school counseling are a lack of infrastructure, time, expertise, and social stigma. Proposed solutions include training for counselors, improving infrastructure, and collaborating with external counselors. This think about emphasizes the significance of comprehensive instruction and early intercession to back the mental well-being of children with uncommon needs, the require for advance investigate to create inventive approaches that can move forward the adequacy of learning.